Metode Bermain dalam Pembelajaran PAI di Kelas III SD IT Nurhidayyah Punggung Kasiak Lubuk Alung - Meri Fitri Yanti; Salmiwati Salmiwati (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research is motivated by several problems that the author found at SD IT Nurhidayyah Punggung Kasiak Lubuk Alung. Problems were found in the implementation of the play method which should be able to eliminate student boredom, drowsiness and noise in the classroom have not been resolved properly because the implementation of the play method is not optimal. The purpose of this study is to find out how the implementation of the play method in Islamic Religious Education learning. This research is qualitative descriptive. The research was located at SD IT Nurhidayyah Punggung Kasiak Lubuk Alung. The primary data source is the PAI teacher of class III of SD IT Nurhidayyah Punggung Kasiak Lubuk Alung and the secondary data is the students of class III of SD IT Nurhidayyah Punggung Kasiak Lubuk Alung. Data collection techniques in this study are observation, interviews and documentation. The results of this study indicate that in the implementation of the play method at SD IT Nurhidayyah Punggung Kasiak Lubuk Alung, several game methods have been carried out such as quiz games, word games and snakes and ladders games. The implementation of the quiz game method in Class III of SD IT Nurhidayyah Punggung Kasiak Lubuk Alung has been carried out well, by explaining the steps of the game. And include all students in the game. The implementation of the method of playing word order has also been carried out well, it is in accordance with the steps of the game and makes the class atmosphere more active. The implementation of the snakes and ladders game method has also been carried out well because it has involved all students in the game thereby reducing boredom in the class, even though there are several game steps that have not been implemented by the teacher.